Attuned HRM systems for social enterprises - Dorado, Silvia (Journal of business ethics, 2022)
This paper is motivated by a puzzling observation made when conducting a case study of ProCredit (PC), a well-known social bank. The HR practices that this social enterprise (SE) adopted to cultivate mission identification were unfavorably impacting its retention rate. Building on prior research and our analysis of the case, we argue the need for SEs to embrace HRM systems that are both mission-identification proactive and employee-retention preemptive. It theorizes that these HRM systems should be attuned to the labor market conditions (e.g., market segmentation and competition for employees) that frame how SEs develop and sustain Person-Organization (P-O) fit. Attuned HRM systems are adapted to labor market conditions and tuned to support SEs’ adeptness to operate against the grain of country and industry norms.